2014
DOI: 10.1007/s00216-014-7859-8
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoresis for total glycosaminoglycan analysis

Abstract: A capillary zone electrophoresis-laser induced fluorescence detection (CZE-LIF) method was developed for the simultaneous analysis of disaccharides derived from heparan sulfate, chondroitin sulfate/dermatan sulfate, hyaluronan and keratan sulfate. Glycosaminoglycans (GAGs) were first depolymerized with the mixture of GAG lyases (heparinase I, II, III and chondroitinase ABC and chondroitinase AC II) and GAG endohydrolase (keratinase II) and the resulting disaccharides were derivatized by reductive amination wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 49 publications
1
18
0
2
Order By: Relevance
“…After digestion of bovine corneal KS with keratanase II, two saturated disaccharide standards, 2S KS (Gal6S(1→4)GlcNAc6S) and NS KS (Gal(1→4)GlcNAc6S), could be obtained [28]. The HPLC-MS results showed that in all egg components examined, the disaccharide 2S KS was undetectable (Table 2, Fig.…”
Section: Results and Analysismentioning
confidence: 99%
“…After digestion of bovine corneal KS with keratanase II, two saturated disaccharide standards, 2S KS (Gal6S(1→4)GlcNAc6S) and NS KS (Gal(1→4)GlcNAc6S), could be obtained [28]. The HPLC-MS results showed that in all egg components examined, the disaccharide 2S KS was undetectable (Table 2, Fig.…”
Section: Results and Analysismentioning
confidence: 99%
“…A capillary zone electrophoresis laser-induced fluorescence detection method [34] was recently developed for the simultaneous analysis of disaccharides derived from all four classes. In this study, we developed a simple method for the simultaneous analysis of 23 internal disaccharides from four GAG classes and 5 nonreducing terminal saccharides from CS using LC-ESI-MS/MS with the SRM mode.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the experiments that could determine unequivocally the origins of specificity cannot be conducted at present for several reasons, which include the need to test vast numbers of structural variants in their pure forms [52]. It is the ability to separate these species in sufficient quantities when using natural HS as a source, despite some progress [53][54][55][56], rather than the problem of sequencing them per se, which hinders progress. Heparin is often employed experimentally as a proxy for HS on account of its structural similarity ( §1) and is considerably more highly charged than HS.…”
Section: Experimental Tools: Polysaccharides and Oligosaccharidesmentioning
confidence: 99%